WACANA STUDI HADIS DI INDONESIA: STUDI ATAS HERMENEUTIKA HADIS MUHAMMAD SYUHUDI ISMAIL - Taufan Anggoro (UIN Siber Syekh Nurjati Cirebon, 2018)
Muhammad Syuhudi Ismail is one of the most influential hadith figures in Indonesia. His thinking in terms of understanding the hadith which is popular with the